2,4-Diaryl-pyrimido[1,2-a]benzimidazole derivatives as novel anticancer agents endowed with potent anti-leukemia activity: Synthesis, biological evaluation and kinase profiling - Shaldam, Moataz A; Hendrychová, Denisa; El-Haggar, Radwan; Vojáčková, Veronika; Majrashi, Taghreed A; Elkaeed, Eslam B; Masurier, Nicolas; Kryštof, Vladimír; Tawfik, Haytham O; Eldehna, Wagdy M (European journal of medicinal chemistry, 2023)
Acute myeloid leukemia (AML) stands as one of the most aggressive type of human cancer that can develop rapidly and thus requires immediate management. In the current study, the development of novel derivatives of pyrimido[1,2-a]benzimidazole (5a-p) as potential anti-AML agents is reported. The prepared compounds 5a-p were inspected for their in vitro anti-tumor activity at NCI-DTP and subsequently 5h was selected for full panel five-dose screening to assess its TGI, LC50 and GI50 values. Compound 5h showed effective anti-tumor activity at low micromolar concentration on all tested human cancer cell lines with GI50 range from 0.35 to 9.43 μM with superior sub-micromolar activity towards leukemia. Furthermore, pyrimido[1,2-a]benzimidazoles 5e-l were tested on a panel ofhuman acute leukemia cell lines, namely HL60, MOLM-13, MV4-11, CCRF-CEM and THP-1, where 5e-h reached single-digit micromolar GI50 values for all the tested cell lines. All prepared compounds were first tested for inhibitory action against the leukemia-associated mutant FLT3-ITD, as well as against ABL, CDK2, and GSK3 kinases, in order to identify the kinase target for the herein described pyrimido[1,2-a]benzimidazoles. However, the examined molecules disclosed non-significant activity against these kinases. Thereafter, a kinase profiling on a panel of 338 human kinases was then used to discover the potential target. Interestingly, pyrimido[1,2-a]benzimidazoles 5e and 5h significantly inhibited BMX kinase. Further investigation for the effect on cell cycle of HL60 and MV4-11 cells and caspase 3/7 activity was also performed. In addition, the changes in selected proteins (PARP-1, Mcl-1, pH3-Ser10) associated with cell death and viability were analyzed in HL60 and MV4-11 cells by immunoblotting.
Keywords: tyrosinkinasa 3 podobná fms; Antineoplastic Agents; pyrimido[1,2-a]benzimidazole; Synthesis; Kinase inhibitors; apoptóza; akutní myeloidní leukemie; Apoptosis; benzimidazoly; Leukemia, Myeloid, Acute; Protein Kinase Inhibitors; Anti-tumorigenic; Anti-leukemic agents; lidé; kinasa 3 glykogensynthasy; Glycogen Synthase Kinase 3; nádorové buněčné linie; Benzimidazoles; Cell Proliferation; protinádorové látky; fms-Like Tyrosine Kinase 3; Humans; Cell Line, Tumor; inhibitory proteinkinas; proliferace buněk